Patent Waiver on Covid Vaccine: Access for all or Global Supply Crisis? (Journal of Intellectual Property Rights (JIPR), 2023)
The Coronavirus disease 2019 or COVID-19, pandemic has transpired disastrous effects in the world in multiple formsranging from the high death tolls to the steep fall in global economy. Even so, it had managed to provide a silver lining inthe form of unanimity of researchers from several disciplines, who united to contribute blood, sweat and tears to present tothe world the miracle of science- vaccines. One can only imagine the extent of investment which has gone into developmentof the few vaccines we have today. In fact the research continues to be in full swing, with the hope and zest to better. Whileevery country fights the pandemic with vigor, it is the pharmaceutical R&D which is expected of breakthrough discoveriesas a solution. Where the pressure to succeed is tremendous, millions invested and no option to fail is it not justified to expectand deserve patent for the same. This paper will dwell into the justification of patent over Covid-19 vaccines, the ongoingdebate over patent waiver and analyze whether the waiver will in fact facilitate greater access and affordability of vaccinesor prove to be an impediment for global supply.